Regional Economic Outlook, April 2011, Sub-Saharan Africa : Recovery and New Risks. (Regional Economic Outlook, 2011)
Sub-Saharan Africa's economic recovery is well under way, although among country groups there is variation in the speed of the recovery. In most of the region's low-income countries and among the seven oil exporters growth is almost back to precrisis levels. However, in the region's middle-income countries, including South Africa, the recovery has been more gradual. This Regional Economic Outlook describes the impact of recent economic developments---sharp increases in food and fuel prices will need fiscal interventions targeting the poor, while higher oil prices will be a boon to some countries and adversely affect others. Policy adjustments are needed to move away from the supportive stance of the last few years but should be balanced against the need to alleviate the impact of rising food prices on poor households.